Double versus single thrombophilias during pregnancy. (2nd October 2018) - Carroll, Rachel; Rebarber, Andrei; Booker, Whitney; Fox, Nathan; Saltzman, Daniel; Lam-Rachlin, Jennifer; Gupta, Simi
Abstract: Objective: The primary objective of this study was to evaluate whether women with double thrombophilias have a greater risk for obstetric complications as compared with women who have single thrombophilias. Study design: This is a retrospective cohort study of all patients in a single practice with a clinically significant inherited thrombophilia and treated with anticoagulation between 2005 and 2013. Thrombophilias evaluated include: factor V Leiden, prothrombin G20210A gene mutation, protein S deficiency, protein C deficiency, and antithrombin III deficiency. Double thrombophilia was defined as the presence of two thrombophilias or homozygosity for factor V Leiden or prothrombin Gene Mutation. Demographic and obstetrical outcome data were collected. Data on all patients with double thrombophilias who met inclusion criteria was reported. Data was then compared between the patients with double thrombophilias and single thrombophilias with singleton gestations. The data was analyzed with Pearson's chi-squared or Student's t-test as appropriate with p value <.05 used for significance. Results: Eighteen patients with clinically significant double thrombophilias who met inclusion criteria were identified. Most patients delivered full term (88.9%) and appropriate for gestational age (77.8%) infants. One hundred thirty-two patients with single thrombophilias and 14 patients with double thrombophilias with singleton gestations were then compared. Demographic characteristics were not significantly different between the two groups. There were no significant differences in obstetrical outcomes between patients. Conclusions: There were no significant differences in obstetrical outcomes for patients with clinically significant double thrombophilias versus single thrombophilias when treated with anticoagulation.